Facile Synthesis of Gold-Supported Thin Film of Cobalt Oxide via AACVD for Enhanced Electrocatalytic Activity in Oxygen Evolution Reaction. (30th November 2018) - Ehsan, Muhammad Ali; Aziz, Md. Abdul; Rehman, Abdul; Hakeem, Abbas Saeed; Qasem, Mohammed Ameen Ahmed; Saadi, Omar Waqas
Abstract : Herein, we report a rapid and facile synthetic methodology for robust, nanostructured films of cobalt oxide over metal evaporated gold layer of 50 nm, directly onto plain glass substrates via aerosol assisted chemical vapor deposition (AACVD) approach. The films thus prepared are characterized by XRD, SEM, and EDX spectroscopy as a function of deposition time (i.e., 5 min – 20 min). It is remarkably shown that the film growth rate is 0.8 nmSec −1 using this AACVD method and a commercially available precursor, which is ∼10 times higher as compared to the electrochemical synthetic routes. As a result, 250 nm thick cobalt oxide films are generated only in 5 minutes of deposition time. The water oxidation reaction for this film started at ∼0.6 V vs Ag/AgCl with current density of 10 mA cm −2 is achieved at ∼0.75 V that corresponds to an overpotential of 484 mV. This current density is further increased to 60 mA cm −2 at ∼1.5 V (vs Ag/AgCl). Electrochemically active surface area (ECSA) calculations are also performed which indicated that the synergy between Au-film acting as electron sink and the cobalt oxide film acting as catalytic layer are more pronounced than the surface area effects.